Effects of Sexual Orientation on Spiritual Psychotherapy for Inpatient, Residential & Intensive Treatment. Issue 1 (3rd February 2022) - Schuttenberg, Eleanor M.; Johnston, Alana M.; Drury, Mia J.; Sneider, Jennifer T.; Silveri, Marisa M.; Rosmarin, David H.
Abstract : Objectives: Spiritual psychotherapy addresses mental health concerns by integrating spirituality/religion into treatment. There is scant research on how such approaches interact with sexual minority status. We sought to identify and compare how sexual minority and heterosexual patients respond to spiritual psychotherapy. Method: We collected data from heterosexual ( n = 66) and sexual minority ( n = 15) patients who self‐referred to participate in Spiritual Psychotherapy for Inpatient Residential & Intensive Treatment (SPIRIT), a spiritually‐integrated, group‐based, cognitive‐behavioral treatment. Results: We did not find significant differences between heterosexual and sexual minority patients across demographic/clinical variables, spiritual/religious characteristics, or effects of SPIRIT. Both groups reported notable perceived benefit of SPIRIT. Conclusions: Although not specifically tailored for sexual minority patients, or intended to reconcile spiritual/religious conflicts around sexual identity, programs like SPIRIT may benefit sexual minority patients by providing a safe space to explore both sexual orientation and religious identity. In turn, this may help sexual minority patients develop frameworks to recruit spirituality/religion in the process of coping with distress, as a catalyst for clinical change. HIGHLIGHTS: To our knowledge, this is the first study to examine responses to spiritually integrated therapy among sexual minority individuals. Sexual minority and heterosexual patients were equivalent with regard to clinical severity, spiritual/religious characteristics, and spiritual distress. Sexual minority and heterosexual individuals benefited equally from spiritually‐integrated therapy. Spiritual/religious involvement and spiritual distress did not differentially predict perceived benefit from spiritually‐integrated psychotherapy among sexual minority or heterosexual patients. Findings underscore the importance of clinicians being open to exploration of relevant spiritual/religious topics with all patients, without assumption that such themes may be inherently problematic for sexual minorities.